Computational fluid dynamic simulation of the resistance of ships in calm water - Goh, Cai Qi (Nanyang Technological University, 2022)
Computation Fluid Dynamic (CFD) analysis is widely used these days. CFD analysis has demonstrated its advantage in simulating a range of situations, such as a ship’s resistance, seakeeping, maneuvering and propulsion, in a very efficient and costsaving manner. There are several types of resistance, for example, calm water resistance, viscous resistance, added resistance, etc. Calm water is the most basic type of resistance a ship will experience. In this report, the student will focus on using the CFD software, FINE/Marine by NUMECA, to analyze the effects of roughness on the resistance of ship model in calm water. The numerical computation used in the solver is on Reynolds-averaged Navier Stokes equation (RANSE) and in order to build the spatial discretization, the finite volume method will be used. Through this report, the student analysed the effect of roughness on a DTMB Combatant by experimenting with the variable Y+. Additional analysis on the effect of velocity is also discussed in this report. It was found that the increase of Y+ value increases the wall thickness of the hull which also increases the total resistance of the ship moving along the x-direction. The findings concluded that roughness plays a significant role in approximating the resistance in calm water, however, velocity is also as important when estimating the resistance.